2009
DOI: 10.1073/pnas.0913668107
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase APC/C-Cdh1 accounts for the Warburg effect by linking glycolysis to cell proliferation

Abstract: Cell proliferation is known to be accompanied by activation of glycolysis. We have recently discovered that the glycolysis-promoting enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase, isoform 3 (PFKFB3), is degraded by the E3 ubiquitin ligase APC/C-Cdh1, which also degrades cell-cycle proteins. We now show in two different cell types (neoplastic and nonneoplastic) that both proliferation and aerobic glycolysis are prevented by overexpression of Cdh1 and enhanced by its silencing. Furthermore, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
134
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(149 citation statements)
references
References 26 publications
12
134
0
3
Order By: Relevance
“…The function of this transient enhancement of glycolytic activity in late G1, which is necessary for cell cycle progression, now requires investigation because glycolysis might be used to generate energy, substrates for macromolecular synthesis, or for both purposes. Our present results obtained in a cancer-derived cell line, together with previous studies in a noncancer cell line (9) and in human T lymphocytes (10), suggest that these same, or similar, mechanisms underlie cell proliferation and enhanced metabolism in normal and neoplastic cells.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The function of this transient enhancement of glycolytic activity in late G1, which is necessary for cell cycle progression, now requires investigation because glycolysis might be used to generate energy, substrates for macromolecular synthesis, or for both purposes. Our present results obtained in a cancer-derived cell line, together with previous studies in a noncancer cell line (9) and in human T lymphocytes (10), suggest that these same, or similar, mechanisms underlie cell proliferation and enhanced metabolism in normal and neoplastic cells.…”
Section: Discussionsupporting
confidence: 54%
“…We have recently found that PFKFB3 is regulated during cell proliferation by APC/C-Cdh1 and that silencing this enzyme prevents cells from entering S phase (9,10). These findings suggest that there is close coordination between cell cycle progression and provision of the raw materials required for its completion.…”
mentioning
confidence: 78%
“…Although there is substantial evidence to support increased glycolysis in tumor versus normal tissue, recently there have been reports indicating that glycolysis is closely linked with the cell cycle and that increased glucose metabolism is a consequence of growth signaling within a cell (normal or tumor) and not necessarily as a result of "rewiring" of a cancer cell (32). Nonetheless, increased glucose metabolism seems to be a hallmark of cancer, which is likely due to their uncontrolled and constant movement through the cell cycle as well as other factors associated with oncogenic transformation (30,33).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of APC/C-Cdh1 enables PFKFB3 to up-regulate glycolysis, thus providing the cell with the glucose essential for the subsequent biosynthesis of macromolecules. Our previous studies (9) were carried out in two cell lines; we therefore decided to investigate whether the same mechanism operates in human proliferating primary cells.…”
mentioning
confidence: 99%
“…Inactivation of APC/C-Cdh1 in G1 of the cell cycle is necessary for initiation of S phase, in which DNA is replicated and chromosomes are duplicated. We have recently found that APC/CCdh1 links cell cycle activity with that of the enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase isoform 3 (PFKFB3) (9,10). PFKFB3-a key regulator of glycolysis (11)-contains a KEN box motif and is thus also broken down by APC/C-Cdh1.…”
mentioning
confidence: 99%